A Summative Content Analysis of Stress and Coping among Parents of Children with Autism. Issue 3 (20th July 2020) - Brown, Matthew; Whiting, Jason; Haque, Afshana; Kahumoku-Fessler, Emily
Abstract: Sixty-nine married couples who had a child with autism spectrum disorder (ASD) described their experiences in an online survey. Using Grounded theory thematic analysis and summative content analysis, three broad categories that encompassed 10 codes emerged from the data. These categories were "Parenting Experience" (range of feelings, emphasis on difficulties, and emphasis on growth), "Impact of Parenting Stress on the Couple Relationship" (both strains upon and growth derived from the couple relationship), and "Coping with Parenting Stress" (ranging from poor coping with no couple communication to healthy coping strategies facilitated by the couple relationship). Implications for research and practice are given.